Development of Assemblr EDU Platform to Increase Spatial Literacy for Grade V Elementary Students in Geometry - Fi Jannatin Aliyah; Nurafni Nurafni (FKIP - Universitas Riau, 2026)
The primary motivations for the study are the poor level of spatial literacy among grade V students in the field of geometry, and the restricted development of Assemblr EDU-based learning resources. The goal of this project is to develop reliable, useful, and efficient educational resources to raise students’ spatial literacy. The ADDIE model was used in this study’s Research and Development (R&D) methodology. This experiment was conducted on a small group consisting of 10 students and a large group consisting of 24 students. Data were collected through validator feedback, expert validation results, teacher and student response questionnaires, pretest, and posttest. The spatial literacy skills measured included spatial visualization, mental rotation, and spatial orientation using cubes and rectangular prisms. The results indicate that, according to media experts 86.4%, content experts 94.4%, and language experts 85%. The results differed significantly according to a paired sample t-test. Spatial literacy skills improved, with an N-Gain score of 0.68 for the small class and 0.82 for the large class. Thus, the Assemblr EDU learning medium can be used as an alternative for teaching mathematics on the topics of cubes and rectangular prisms to improve the spatial literacy of elementary school students.